1997
DOI: 10.1093/jnci/89.6.437
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase Activity in Benign and Malignant Epithelial Ovarian Tumors

Abstract: The presence of telomerase expression in ovarian LMP tumors supports the merit of continuing to separate these tumors from cystadenomas, in spite of their apparent benign clinical course. The finding of telomerase expression in papillary cystadenomas suggests that such tumors may be mechanistically related to LMP tumors and should perhaps be reclassified as variants of LMP tumors. Lack of telomerase expression in ovarian cystadenomas raises questions about the alleged immortality of these tumors because expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
21
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 19 publications
3
21
1
Order By: Relevance
“…Usually, there is no detectable telomerase activity in normal ovarian tissue. In benign ovarian pathologies such as mucinous cyst adenoma, the positivity of telomerase activity was found to be between 0% and 36.3% in association with proliferation (19)(20)(21)(22). In the same trials, 67% to 100% telomerase activity was detected in borderline tumors.…”
Section: Discussionmentioning
confidence: 83%
“…Usually, there is no detectable telomerase activity in normal ovarian tissue. In benign ovarian pathologies such as mucinous cyst adenoma, the positivity of telomerase activity was found to be between 0% and 36.3% in association with proliferation (19)(20)(21)(22). In the same trials, 67% to 100% telomerase activity was detected in borderline tumors.…”
Section: Discussionmentioning
confidence: 83%
“…Most LMP tumours express telomerase in vivo, providing an additional argument in support of the notion that they represent a stage of malignant transformation that is distinct from cystadenomas (Wan et al, 1997). Given that telomere attrition is thought to be associated with structural chromosomal instability that can be overcome by telomerase (Counter et al, 1992;Artandi et al, 2000;O'Hagan et al, 2002), one may question whether the increased stability observed in our cultured LMP tumour cells could have been due to varying levels of telomerase expression.…”
Section: Discussionmentioning
confidence: 64%
“…For example, although somatic loss of heterozygosity, a hallmark of malignancy, has been occasionally observed in LMP tumours, it is clear that such events are not only rare in these tumours, but are also not essential to their development (Cheng et al, 1996). On the other hand, LMP tumours usually express telomerase (Wan et al, 1997), a feature of the malignant phenotype, and global DNA methylation changes (Cheng et al, 1997) or changes in the DNA methylation status of centromeric and juxtacentromeric sequences (Qu et al, 1999) in these tumours are more similar to those in carcinomas than in cystadenomas. Although these results strengthen the notion that LMP tumours are intermediate between benign and frankly malignant ovarian epithelial tumours, they shed little light on their underlying mechanisms.…”
mentioning
confidence: 99%
“…Cell pellets from peritoneal washings were lysed and tested for the presence or absence of telomerase activity using the telomerase repeat amplification protocol (TRAP; Ref. 23) assay as described previously (25). The reaction products were electrophoresed on 8% polyacrylamide and visualized by autoradiography.…”
Section: Methodsmentioning
confidence: 99%
“…Each assay was performed in parallel with two control reactions, one in which the assay was preceded by digestion of the sample with RNase A (catalog number R5503; Sigma Chemical Co., St. Louis, MO) at a final concentration of 0.05 mg/ml, and another in which 1 l of a cell lysate previously shown to contain high levels of telomerase activity was added to the test sample. A sample was not scored as positive unless the RNase A-treated control showed complete absence of telomerase products because telomerase is a riboprotein that is inactivated by RNase A. Conversely, a sample was not scored as negative unless products were detected after addition of a telomerase-positive extract to that sample (25).…”
Section: Methodsmentioning
confidence: 99%